Analisis Antropometri Dan Koordinasi Mata Tangan Terhadap Keterampilan Pointing Atlet Petanque Sulawesi Selatan - Nurul Natasya; Sudirman Sudirman; Ahmad Rum; Saharullah Saharullah; Muh. Adnan Hudain (Journal on Education, 2024)
This research is a type of quantitative descriptive research that uses a "correlational" research plan. This research aims to find out: (1) the Anthropometric level of Petanque athletes in South Sulawesi. (2) the hands-eyes coordination level of Petanque athletes in South Sulawesi, (3) the correlation between Anthropometrics and the pointing skills of Petanque athletes in South Sulawesi. The research population were petanque athletes in South Sulawesi with the total of 50 athletes, while the research samples were petanque athletes in South Sulawesi, totaling 25 female athletes. The data collection technique employed descriptive statistical analysis. The results of anthropometric of petanque athletes in South Sulawesi is in very poor category with a percentage of 0% (0 athletes), poor category by 32% (8 athletes), moderate category by 32% (8 athletes), good category by 24% (6 athletes), and very good category by 12% (3 athletes). Based on the average score, namely 105.04, the anthropometric result of petanque athletes in South Sulawesi is in moderate category. The hands-eyes coordination of petanque athletes in South Sulawesi is in very poor category with a percentage of 0% (0 athletes), poor category by 36% (9 athletes), moderate category by 36% (9 athletes), good category by 24% (6 athletes), and very good category by 4% (1 athlete). Based on the average score, namely 14.28 points, the result of hands-eyes coordination analysis of petanque athletes in South Sulawesi is in moderate category. The pointing skills of petanque athletes in South Sulawesi are in very poor category with a percentage of 4% (1 athlete), poor category by 36% (9 athletes), moderate category by 20% (5 athletes), good category by 40% (10 athletes), and very good category by 0% (0 athletes). Based on the average score, namely 10.72, the result of pointing skills analysis is in moderate category.